Germinal centre B cell and T follicular helper cell responses to viral vector and protein-in-adjuvant vaccines - Wang, C; Hart, M; Chui, C; Ajuogu, A; Brian, IJ; de Cassan, SC; Borrow, P; Draper, SJ; Douglas, AD (American Association of Immunologists, 2016)
There is great interest in the development of antibody-inducing subunit vaccines targeting infections including HIV, malaria and Ebola. We previously reported that adenovirus vectored vaccines are potent in priming antibody responses, but uncertainty remains regarding the optimal approach for induction of humoral immune responses. Here, using ovalbumin as a model antigen, we assessed the magnitude of the primary and anamnestic antigen-specific IgG responses of mice to four clinically-relevant vaccine formulations: replication-deficient adenovirus; modified vaccinia Ankara (MVA, a poxvirus); protein with alum; and protein in the squalene oil-in-water adjuvant Addavax. We then used flow cytometric assays capable of measuring total and antigen-specific germinal center (GC) B cell and follicular helper T cell (Tfh) responses to compare the induction of these responses by the different formulations. We report that adenovirus vectored vaccines induce antigen insert-specific GC B cell and antibody responses of a magnitude comparable to those induced by a potent protein/ squalene oil-in-water formulation whereas- despite a robust overall GC response - the insertspecific GC B cell and antibody responses induced by MVA were extremely weak. Antigenspecific Tfh responses to adenovirus vectored responses exceeded those induced by other platforms at day 7 after immunization. We found little evidence that innate immune activation by adenovirus may act as an adjuvant in such a manner that the humoral response to a recombinant protein may be enhanced by co-administering with an adenovirus lacking a transgene of interest. Overall, these studies provide further support for the use of replication-deficient adenoviruses to induce humoral responses.